Assessing Self-Instructional Module Efficacy for Disaster Management Knowledge Among Maharashtra School Teachers - Sharma, Shiwangi (Journal of Social Science and Humanities, 2025)
Background Of Study: Disaster can affect anyone, but children are the most vulnerable. School play an essential rile during disasters because children spend most of their time in such institutions, and teachers are among the untapped groups whose potential roles in disaster risk reduction and management are not yet fully realizes.1Disaster is defined as phenomena caused by environmental events or armed conflicts that lead to fatalities, injuries, stress, physical damage and economic breakdown of great significance. They occur on a scale that overwhelms local resources, usually requiring external assistance. Improving the effectiveness and efficiency of interventions, and the fairness of their distribution, is crucial in the field of disaster response. For that reason, increasing and improving the scientific evidence for disaster relief is essential. Research is also vital to accurately describe phenomena in disaster, also called humanitarian emergencies or crise. Problem Statement: ‘‘A study to assess effectiveness of self - instructional module (SIM) on knowledge regarding disaster management among school teachers in selected schools of Maharashtra. Objectives of the Study: 1. To assess the existing level of knowledge regarding disaster management among school teachers in selected schools of Maharashtra.2. To determine the effectiveness of self - instructional module on the level of knowledge regarding disaster management among school teachers in selected schools of Maharashtra.3. To find out association between pre - test levels of knowledge on disaster management with selected socio demographic variables. Methodology: Pre experimental research design, one group pre - test post - test research design was used to assess the effectiveness of Self - Instructional Module regarding Disaster Management among school teachers in selected school of Maharashtra. In this study 60 samples selected Non - Probability Purposive Sampling technique. The data obtained were analysed using descriptive and inferential statistics based on objectives and research questions of the study. Analysis and Result: In the school teachers with respect to the age majority 29 (48.9%) of the teachers belongs to 41 - 50 years, 25 (41.7%) of teachers belongs to 31 - 40 years, 5 (8.3%) of teachers from 51 and above year and only 1 (1.7%) was in from 21 - 30 year of age. In case of gender majority 35 (58.3%) were male and 25 (41.7%) were female. Regarding education status of the school teachers the majority 43 (71.7%) were educated up to B. Ed., 13 (21.7%) were M. Ed. and 4 (6.7%) were educated up to D. Ed. The majority 23 (38.3%) teachers having 11 - 15 years’ experience in teaching, 18 (30.0%) are having 6 - 10 years’ experience and 19 (31.7%) are having 16 years and above experience in teaching. Majority 38 (63.3%) were used T. V. as source of knowledge regarding disaster management. and 22 (36.7%) were used newspaper as source of knowledge regarding disaster management. Knowledge wise comparison of study subject in pre - test revels 30 (50.0%) were had poor knowledge regarding disaster management, 24 (40.0%) were had average knowledge regarding disaster management and 6 (10.0%) teachers were had good knowledge regarding disaster management. In the post - test result 0 (0.0%) were had poor knowledge regarding disaster management, 0 (0.0%) were had average knowledge regarding disaster management and 60 (100.0%) teachers were had good knowledge regarding disaster management. There is no significance association between knowledge score and demographic variables. Conclusion: After the present study to assess effectiveness of Self Instructional Module regarding disaster management among school teachers, study proves that having the need to improve the knowledge regarding disaster management. And also the Self Instructional Module is effective for to improve knowledge.